Digital Media Impact on Sufi Practices: Analyzing Ijāza Wirid Dhikr - Rizki, Ahmad; Rusdi, Hasan (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
This article discusses the impact of digital media on Sufi practices, specifically in the context of conducting ijāza (authorization) for wird dhikr rituals through digital platforms. Traditionally, Sufi practices such as the ijāza involve direct teaching from teacher to student. However, with the rapid development of digital media, the ijāza process has undergone significant changes. This study adopts an eclectic approach, which combines digital ethnography to study online participant engagement and a comprehensive literature review to track and measure the transformation of ijāza through digital media. Data were gathered from various sources, including books, scholarly journals, and relevant digital content related to the research topic. The findings show that the evolution of digital media has transformed the implementation of ijāza for wird dhikr from direct (traditional) to indirect transmission through online media, and it is considered valid. Yet, ijāza is not merely dealing with the process of authorization but also the transmission of blessings and spiritual knowledge from the teacher to the student, which needs close engagement and relationships that can only be achieved with direct interaction.Contribution: This article provides an understanding of the impact and validity of ijāza conducted through digital media compared to traditional methods yet considered valid.